Predictors of warfarin non-adherence in younger adults after valve replacement surgery in the South Pacific. Issue 2 (14th June 2016) - Thomson Mangnall, Linda J; Sibbritt, David W; Al-Sheyab, Nihaya; Gallagher, Robyn D
Abstract : Objectives: Globally, mechanical valves are predominant as replacements for adolescents and younger adults with rheumatic heart disease (RHD). Mechanical valve implantation necessitates lifelong antithrombotic management (warfarin) and associated lifestyle modification, with event-free survival largely dependent on international normalised therapeutic ratios (INRs) remaining within the target therapeutic range. There is limited information on factors that may influence warfarin adherence among younger people or those in resource-limited settings. This study sought to identify predictors of warfarin adherence after valve replacement surgery for RHD in Fiji (n=127). Methods: A cross-sectional study design was used. Results: The sample had a mean age of 31.23 years (SD 13.34) and a mean time-since-surgery of 3.72 years (SD 3.95). Just over half were women (n=71, 56%) and almost two-thirds were indigenous (I-taukei, n=78, 61%). Most had an isolated valve procedure (n=94, 74%) and at the time of survey, they were in New York Heart Association Class I (n=97, 76%). A quarter (n=33, 26%) reported poor adherence with anticoagulation therapy and 13.38% (n=17) reported complete warfarin cessation. While younger age was significantly associated with non-adherence to warfarin therapy (p=0.008), the independent predictors of people who discontinue warfarin completely were those not understanding why warfarin was needed (OR=9.97, p=0.006); a history of forgetting to take warfarin (OR=8.64, p=0.0013) and travel time to heart clinic >1 hour (OR=5.80, p=0.039). Conclusions: While medication adherence is complex and multifactorial, the consequences of warfarin non-adherence are potentially catastrophic. These results provide an important first step towards the development of country-specific and disease-specific strategies to improve warfarin adherence.